Microsphere-containing cross-linked hyaluronic acid or salt thereof as well as preparation method and application thereof

By introducing microspheres before cross-linking of hyaluronic acid or its salts, and using POSECROSS technology to form multiple soft elastic chimeric structures, the problem of excessively rapid degradation of microspheres and incompatibility with tissues in the prior art is solved, and better microsphere protection and collagen regeneration effects are achieved.

CN119708553APending Publication Date: 2025-03-28IMEIK TECH DEV CO LTD

Patent Information

Application Number
CN202411911887.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art cannot take into account the simplicity, safety, crosslinker removal effect, viscosity and cohesion of the hyaluronic acid gel preparation process, and it is difficult to effectively protect microspheres, resulting in excessive degradation of microspheres and incompatible with tissues, causing inflammation problems.

Method used

Using POSECROSS technology, microspheres are introduced before crosslinking hyaluronic acid or their salts to form crosslinked hyaluronic acid or their salt gels containing microspheres. The dispersion and encapsulation of microspheres are improved through multiple soft elastic chimeric structures, and the degradation time of microspheres and the effect of collagen regeneration is extended.

Benefits of technology

It achieves better dispersion and encapsulation of microspheres, extends the degradation time of microspheres and the effect of collagen regeneration, improves the structural stability and long-term stability of the composition, and reduces the degradation and inflammatory response of microspheres.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708553A_ABST
    Figure CN119708553A_ABST
Patent Text Reader

Abstract

The invention discloses cross-linked hyaluronic acid containing microspheres or salts thereof as well as a preparation method and application of the cross-linked hyaluronic acid. According to the invention, HA with high molecular weight and HA with low molecular weight are respectively crosslinked under the conditions of large amount of aqueous alkali and small amount of aqueous alkali, microsphere components are respectively introduced before crosslinking, and the hyaluronic acid with high molecular weight and the hyaluronic acid with low molecular weight or salts thereof form a loose structure containing microspheres under the condition of large amount of aqueous alkali. The low-molecular-weight hyaluronic acid or the salt thereof forms a compact rubber ball mixed network structure under the condition of a small amount of an alkali solution, and then the two are mixed and continuously crosslinked, so that the overall structure is more compact, the microspheres can be more uniformly dispersed in the formed multiple network structure, the elastic modulus of the system is improved, the microspheres can be more effectively wrapped, and the service life of the system is prolonged. After moist heat sterilization, the loss rate of elastic modulus is low, the change of pH caused by microsphere degradation is small, and the degradation time of the microspheres after being implanted into a body is prolonged, so that the effect of stimulating collagen regeneration by the microspheres is prolonged, and the overall stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomaterials, and specifically relates to a cross-linked hyaluronic acid or a salt thereof containing microspheres, and a preparation method and application thereof. Background Art

[0002] Hyaluronic acid is a natural mucopolysaccharide, composed of (1-β-4) D-glucuronic acid and (1-β-3) N-acetyl-D-aminoglucose disaccharide units repeatedly connected. It is an important component of human and animal skin, vitreous body, joint lubricating fluid and cartilage tissue. Sodium hyaluronate has multiple functions in the human body, including: space filling, hydration, joint lubrication, and providing a matrix through which cells can migrate. Although hyaluronic acid has many advantages, the weak mechanical properties of natural hyaluronic acid and its easy degradation in the body limit its application in biomaterials. Cross-linked sodium hyaluronate is a polymer gel obtained by chemical cross-linking of sodium hyaluronate, which makes up for the short retention time of natural sodium hyaluronate.

[0003] Patent document CN106279726B discloses a cross-linked sodium hyaluronate gel and a preparation method thereof. Under ultrasonic conditions, a cross-linking agent is added dropwise to an alkaline aqueous solution of sodium hyaluronate to carry out a cross-linking reaction. After the reaction is completed, the pH value of the system is adjusted to 7.1-7.5 with an acid, stirred for 1-2 hours, and then precipitated with anhydrous ethanol to obtain a cross-linked sodium hyaluronate gel. However, this method does not have a step of removing the cross-linking agent, which easily causes the cross-linking agent to remain.

[0004] Patent document CN112940300B discloses a method for preparing a cross-linked hyaluronic acid gel, comprising the following steps:

[0005] (1) Mixing an aqueous solution containing a crosslinking agent and hyaluronic acid, a metal salt thereof, or a mixture thereof in a non-neutral environment to form a mixed solution; (2) placing the mixed solution at a temperature lower than 0°C and higher than the eutectic point of the mixed solution and maintaining the temperature for a time sufficient to form a solid-liquid heterogeneous system; (3) placing the heterogeneous system at a temperature lower than 0°C and higher than the eutectic point of the mixed solution to perform a crosslinking reaction; (4) melting the solid phase in the heterogeneous system after the crosslinking reaction, and optionally neutralizing, purifying, and homogenizing. However, the neutralization step described in this method cannot ensure that the pH of the system decreases more gently, thereby easily destroying the three-dimensional crosslinked structure of the sodium hyaluronate gel system.

[0006] Polyester microspheres, collagen microspheres, silk fibroin microspheres, hydroxyapatite microspheres, etc. are usually used as a new type of medical and aesthetic filling material due to their biocompatibility, biodegradability and non-toxicity. However, when the microspheres currently studied are mixed with carriers such as matrices and sterilized, the carriers cannot protect the microspheres well, so that after the product is injected and filled, the microspheres are still prone to problems such as rapid degradation, incompatibility with the tissues at the injection site, and inflammation.

[0007] In summary, the existing technology cannot take into account the industrialization requirements of hyaluronic acid gel, such as simple preparation process, good safety, effective removal of cross-linking agents, strong viscosity, high cohesion, and low water absorption. It is also difficult to effectively ensure the degradation effect of microspheres and achieve collagen regeneration. Summary of the invention

[0008] The present invention overcomes the defects existing in the prior art, and provides a cross-linked hyaluronic acid or its salt containing microspheres and a preparation method and application thereof. Through the POSS technology (Polybasic Overlapping Soft Elastic Cross-linking Technology, abbreviated as POSS technology), microspheres are introduced before the cross-linking of hyaluronic acid or its salt to obtain a cross-linked hyaluronic acid or its salt gel containing microspheres, and the microspheres can participate in the formation of multiple soft elastic mosaic structures, thereby achieving better dispersibility and encapsulation of the microspheres in the gel, and can effectively protect the microspheres during wet heat sterilization, reduce the degradation of the microspheres, and prolong the degradation time of the microspheres implanted in the body, thereby prolonging the effect of the microspheres stimulating collagen regeneration.

[0009] The first aspect of the present invention provides a cross-linked hyaluronic acid or a salt thereof containing microspheres, and the preparation method of the cross-linked hyaluronic acid or a salt thereof containing microspheres comprises the following steps:

[0010] (1) mixing hyaluronic acid I or its salt, hyaluronic acid II or its salt, a first alkaline solution, microspheres and a cross-linking agent, and reacting them to obtain a cross-linked hyaluronic acid I′ or its salt;

[0011] (2) mixing hyaluronic acid III or its salt, a second alkaline solution, microspheres and a cross-linking agent, and reacting them to obtain cross-linked hyaluronic acid II′ or its salt;

[0012] (3) After diluting the cross-linked hyaluronic acid I′ or its salt obtained in step (1) with water, add the cross-linked hyaluronic acid II′ or its salt and hyaluronic acid IV or its salt obtained in step (2), mix and react, and obtain the cross-linked hyaluronic acid or its salt containing microspheres.

[0013] Furthermore, the mass concentration of the first alkaline solution is higher than the mass concentration of the second alkaline solution.

[0014] Furthermore, the molecular weight of the hyaluronic acid I or its salt is higher than the molecular weight of the hyaluronic acid II, III, IV or its salt.

[0015] Further, the concentration of the first alkaline solution in step (1) is 10 to 100 mg / mL (e.g., 10 mg / mL, 15 mg / mL, 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, 36 mg / mL, 37 mg / mL, 38 mg / mL, 39 mg / mL, 40 mg / mL, 41 mg / mL, 42 mg / mL, 43 mg / mL, 44 mg / mL, 45 mg / mL, 46 mg / mL, 47 mg / mL, 48 mg / mL, 49 mg / mL, 50 mg / mL, 51 mg / mL, 52 mg / mL, 53 mg / mL, 54 mg / mL, 55 mg / mL, 56 mg / mL, 57 mg / mL, 58 mg / mL, 59 mg / mL, 60 mg / mL, 61 mg / mL, 62 mg / mL, 63 mg / mL, 64 mg / mL, 65 mg / mL, 66 mg / mL, 67 mg / mL, 68 mg / mL, 69 mg / mL, 70 mg / mL, 71 mg / mL, 72 mg / mL, 73 mg / mL, 74 mg / mL 7mg / mL, 48mg / mL, 49mg / mL, 50mg / mL, 51mg / mL, 52mg / mL, 53mg / mL, 54mg / mL, 55mg / mL, 56mg / mL, 57mg / mL , 58 mg / mL, 59 mg / mL, 60 mg / mL, 70 mg / mL, 80 mg / mL, 90 mg / mL, 100 mg / mL), preferably 12 to 90 mg / mL, more preferably 15 to 80 mg / mL.

[0016] Further, in step (2), the concentration of the second alkaline solution is 0.1-50 mg / mL (such as 0.1 mg / mL, 1 mg / mL, 5 mg / mL, 10 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, 20 mg / mL, 21 mg / mL, 22 mg / mL, 23 mg / mL, 24 mg / mL, 25 mg / mL, 26 mg / mL, 27 mg / mL, 28 mg / mL, 29 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL), preferably 1-40 mg / mL, and more preferably 5-30 mg / mL.

[0017] Furthermore, the molecular weight of the hyaluronic acid I or its salt is 900-3000 kDa (such as 900 kDa, 950 kDa, 1000 kDa, 1100 kDa, 1200 kDa, 1300 kDa, 1400 kDa, 1500 kDa, 1600 kDa, 1700 kDa, 1800 kDa, 1900 kDa, 2000 kDa, 2500 kDa, 3000 kDa), preferably 1000-2000 kDa, and more preferably 1200-1600 kDa.

[0018] In one embodiment of the present invention, the molecular weight of the hyaluronic acid I or its salt is 1500 kDa.

[0019] Further, the molecular weight of the hyaluronic acid II, III, IV or its salt is 100-1000 kDa (such as 100 kDa, 150 kDa, 200 kDa, 250 kDa, 300 kDa, 350 kDa, 400 kDa, 450 kDa, 500 kDa, 550 kDa, 560 kDa, 570 kDa, 580 kDa, 590 kDa, 600 kDa, 610 kDa, 620 kDa, 630 kDa, 640 kDa, 650 kDa, 700 kDa, 750 kDa, 800 kDa, 850 kDa, 900 kDa, 1000 kDa), preferably 300-800 kDa, and more preferably 400-700 kDa.

[0020] Furthermore, the molecular weights of the hyaluronic acid II, III, IV or their salts may be the same or different.

[0021] In one embodiment of the present invention, the molecular weight of the hyaluronic acid II, III, IV or its salt is 600 kDa.

[0022] Furthermore, in step (1), the mass ratio of hyaluronic acid I or its salt to hyaluronic acid II or its salt is 2-10:1, preferably 3-9:1.

[0023] In one embodiment of the present invention, the mass ratio of hyaluronic acid I or its salt to hyaluronic acid II or its salt in step (1) is 3:1.

[0024] Furthermore, the mass ratio of the cross-linked hyaluronic acid I′ or its salt to the cross-linked hyaluronic acid II′ or its salt is 1-10:1; preferably 2-6:1.

[0025] Furthermore, the amount of hyaluronic acid IV or its salt added is 5%-30% of hyaluronic acid I or its salt relative to hyaluronic acid I or its salt.

[0026] Furthermore, water is added in step (3) to dilute the alkaline solution to a concentration equal to the concentration of the second alkaline solution in step (2).

[0027] Furthermore, the reaction temperature in steps (1), (2) and (3) is 20 to 30°C.

[0028] Furthermore, the reaction time in steps (1), (2) and (3) is 4 to 30 hours.

[0029] Furthermore, the reaction temperature and time in steps (1), (2) and (3) may be the same or different.

[0030] In one embodiment of the present invention, the reaction temperature in step (1) is 25° C. and the reaction time is 20 h.

[0031] Furthermore, the hyaluronic acid I or its salt, hyaluronic acid II or its salt, hyaluronic acid III or its salt and hyaluronic acid IV or its salt can be derived from animals or obtained through bacterial fermentation.

[0032] Further, the hyaluronate is selected from any one of sodium hyaluronate (HA), potassium hyaluronate, calcium hyaluronate, magnesium hyaluronate, ammonium hyaluronate, tetrabutylammonium hyaluronate, bismuth hyaluronate and zinc hyaluronate; preferably sodium hyaluronate.

[0033] Furthermore, the alkaline solution is selected from: sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium sulfite, potassium sulfite, or a solution prepared by one or more thereof, preferably sodium hydroxide solution. The first alkaline solution and the second alkaline solution may be the same or different; preferably, the first alkaline solution and the second alkaline solution are the same.

[0034] Furthermore, the cross-linking agent is selected from: one or a combination of two or more of 1,4-butanediol diglycidyl ether (BDDE), divinyl sulfone, polyethylene glycol, genipin and carbodiimide, preferably 1,4-butanediol diglycidyl ether.

[0035] Furthermore, the cross-linking degree of the obtained cross-linked hyaluronic acid or its salt containing microspheres is 1% to 6%, preferably 1.5% to 5%.

[0036] Furthermore, the microspheres are selected from: one or more of polyester microspheres, collagen microspheres, silk fibroin microspheres, and hydroxyapatite microspheres; preferably polyester microspheres; more preferably, the polyester microspheres are one or more of left-handed polylactic acid PLLA, right-handed polylactic acid PDLA, racemic polylactic acid PDLLA, polylactic acid co-glycolic acid PLGA, polymethyl methacrylate PMMA, polycaprolactone PCL, left-handed lactic acid-ethylene glycol copolymer PEG-PLLA, and hydroxyapatite-left-handed polylactic acid HAP-PLLA.

[0037] Further, the content of microspheres in the cross-linked hyaluronic acid or its salt containing microspheres is: 10% to 75% (such as 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, 38%, 40%, 42%, 44%, 45%, 46%, 48%, 50%, 52%, 54%, 55%, 56%, 58%, 60%, 62%, 64%, 65%, 66%, 68%, 70%, 72%, 74%, 75%), preferably 15% to 70%, more preferably 20% to 65%.

[0038] Furthermore, the dosage ratio of the microspheres in steps (1) and (2) is 1-5:1 (e.g., 1:1, 2:1, 3:1, 4:1, 5:1).

[0039] The present invention adopts high-molecular-weight HA and low-molecular-weight HA to be cross-linked under the condition of large amount of alkaline solution and small amount of alkaline solution, and introduces microsphere components respectively before cross-linking. The large amount of alkaline solution can fully destroy the hydrogen bonding effect between HA, so that the high-molecular-weight and low-molecular-weight HA molecular chains are fully extended and stretched, and the molecular chains of low-molecular-weight HA can freely perform irregular translation or rotational motion while stretching. The high-molecular-weight and low-molecular-weight HA form interlaced cross-linking, so that the low-molecular-weight HA can be interlaced or erected between the high-molecular-weight HA, and a scaffold structure can be formed, which is convenient for the microspheres to enter the gel network. At the same time, the large amount of alkaline solution causes a certain degradation of the molecular weight of HA, thereby cross-linking to form a loose structure with a large mesh spacing. In the HA cross-linking process, the microspheres can be evenly embedded in the loose structure, and the rigid microspheres are wrapped in the gel network, thereby enhancing the supporting performance of the gel; then, under the condition of a small amount of alkaline solution, the microspheres are uniform ... When low molecular weight HA is used as the raw material, molecular chain entanglement is more common, and it is easy to react to form a compact gel ball mixed network structure, and then the compact gel ball mixed network structure is further cross-linked with the aforementioned loose structure to make the overall structure more compact, and the microspheres can be more evenly dispersed in the formed multiple network structure, thereby increasing the loading capacity of the microspheres, so that the loading capacity of the microspheres can be as high as 75%; the presence of rigid balls in the gel not only increases the elastic modulus of the system, but also the multiple network structure can more effectively wrap the microspheres, which is more conducive to the moisture and heat sterilization resistance of the composition. The loss rate of elastic modulus after sterilization is low, which can more effectively protect the microspheres and reduce the degradation of the microspheres, so that the pH change caused by the degradation of the microspheres is smaller, and the degradation time and safety performance of the microspheres after implantation in the body are prolonged, thereby prolonging the effect of the microspheres in stimulating collagen regeneration, and also improving the suspension performance of the microspheres in the composition, that is, the overall structural stability and long-term stability of the composition.

[0040] The second aspect of the present invention provides a composition, which comprises: the cross-linked hyaluronic acid or its salt containing microspheres of the first aspect, and also comprises non-cross-linked hyaluronic acid or its salt, phosphate buffer, optional local anesthetic and / or water-soluble cellulose.

[0041] Furthermore, the mass concentration of the cross-linked hyaluronic acid or its salt in the composition is 8-30 mg / mL (such as 8 mg / mL, 9 mg / mL, 10 mg / mL, 10.5 mg / mL, 11 mg / mL, 11.5 mg / mL, 12 mg / mL, 12.5 mg / mL, 13 mg / mL, 13.5 mg / mL, 14 mg / mL, 14.5 mg / mL, 15 mg / mL, 15.5 mg / mL, 16 mg / mL, 16.5 mg / mL, 17 mg / mL, 17.5 mg / mL, 18 mg / mL, 18.5 mg / mL, 19 mg / mL, 19.5 mg / mL, 20 mg / mL), preferably 10-27 mg / mL, more preferably 12-25 mg / mL.

[0042] Furthermore, the non-cross-linked hyaluronate is selected from any one of non-cross-linked sodium hyaluronate, non-cross-linked potassium hyaluronate, non-cross-linked calcium hyaluronate, non-cross-linked magnesium hyaluronate, non-cross-linked ammonium hyaluronate, non-cross-linked tetrabutylammonium hyaluronate, non-cross-linked bismuth hyaluronate and non-hyaluronate zinc, preferably non-cross-linked sodium hyaluronate.

[0043] Further, the concentration of the non-cross-linked hyaluronic acid or its salt is 0.2-10 mg / mL (such as 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, 1.4 mg / mL, 1.5 mg / mL, 1.6 mg / mL, 1.7 mg / mL, 1.8 mg / mL, 1.9 mg / mL, 2 mg / mL, 2.5, 3 mg / mL, 3.5, 4 mg / mL, 4.5 mg / mL, 5 mg / mL, 5.5 mg / mL, 6 mg / mL, 6.5 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL), preferably 0.5-8 mg / mL, more preferably 1-6 mg / mL.

[0044] Further, the molecular weight of the non-cross-linked hyaluronic acid or its salt is 100-1000 kDa (such as 100 kDa, 150 kDa, 200 kDa, 250 kDa, 300 kDa, 350 kDa, 400 kDa, 450 kDa, 500 kDa, 550 kDa, 560 kDa, 570 kDa, 580 kDa, 590 kDa, 600 kDa, 610 kDa, 620 kDa, 630 kDa, 640 kDa, 650 kDa, 700 kDa, 750 kDa, 800 kDa, 850 kDa, 900 kDa, 1000 kDa), preferably 300-800 kDa, and more preferably 400-700 kDa.

[0045] Furthermore, the phosphate buffer comprises: disodium hydrogen phosphate, sodium dihydrogen phosphate and potassium chloride.

[0046] Further, the concentration of the sodium hydrogen phosphate is 0.01 to 10 mg / mL (e.g., 0.01 mg / mL, 0.02 mg / mL, 0.03 mg / mL, 0.04 mg / mL, 0.05 mg / mL, 0.06 mg / mL, 0.07 mg / mL, 0.08 mg / mL, 0.09 mg / mL, 1 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, 1.4 mg / mL). , 1.5 mg / mL, 1.6 mg / mL, 1.7 mg / mL, 1.8 mg / mL, 1.9 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL), preferably, the concentration of the sodium hydrogen phosphate is 3 to 10 mg / mL, more preferably, the concentration of the sodium hydrogen phosphate is 4 to 8 mg / mL.

[0047] In one embodiment of the present invention, the concentration of disodium hydrogen phosphate is 10 mg / mL.

[0048] Further, the concentration of the sodium dihydrogen phosphate is 0.01-9 mg / mL (such as 0.01 mg / mL, 0.02 mg / mL, 0.03 mg / mL, 0.04 mg / mL, 0.05 mg / mL, 0.06 mg / mL, 0.07 mg / mL, 0.08 mg / mL, 0.09 mg / mL, 1 mg / mL, 1.5, 2 mg / mL, 2.5, 3 mg / mL, 3.5, 4 mg / mL, 4.5 mg / mL, 5 mg / mL, 5.5 mg / mL, 6 mg / mL, 6.5 mg / mL, 7 mg / mL, 7.5 mg / mL, 8 mg / mL, 8.5 mg / mL, 9 mg / mL), preferably, the concentration of the sodium dihydrogen phosphate is 1-7 mg / mL, further preferably, the concentration of the sodium dihydrogen phosphate is 2-6 mg / mL.

[0049] In one embodiment of the present invention, the concentration of sodium dihydrogen phosphate is 4 mg / mL.

[0050] Further, the concentration of potassium chloride is 0.01-7 mg / mL (such as 0.01 mg / mL, 0.02 mg / mL, 0.03 mg / mL, 0.04 mg / mL, 0.05 mg / mL, 0.06 mg / mL, 0.07 mg / mL, 0.08 mg / mL, 0.09 mg / mL, 1 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, 1.4 mg / mL, 1.5 mg / mL). L, 1.6 mg / mL, 1.7 mg / mL, 1.8 mg / mL, 1.9 mg / mL, 2 mg / mL, 2.5, 3 mg / mL, 3.5, 4 mg / mL, 4.5 mg / mL, 5 mg / mL, 5.5 mg / mL, 6 mg / mL, 6.5 mg / mL, 7 mg / mL), preferably, the concentration of potassium chloride is 0.05-5 mg / mL, more preferably, the concentration of potassium chloride is 0.1-3 mg / mL.

[0051] In one embodiment of the present invention, the concentration of potassium chloride is 1 mg / mL.

[0052] Furthermore, the local anesthetic is selected from the group consisting of: amide type and ester type or a combination thereof.

[0053] Further, the local anesthetic is selected from: lidocaine or its salt, bupivacaine or its salt, butancaine or its salt, carticaine or its salt, cinchocaine or its salt, chlorocaine or its salt, ethyl p-piperidyl acetylaminobenzoate or its salt, etidocaine or its salt, mepivacaine or its salt, oxethicaine or its salt, prilocaine or its salt, ropivacaine or its salt, tolicaine or its salt, trimecaine or its salt, vardocaine or its salt, articaine or its salt, levobupivacaine or its salt, amicaine or its salt, cocaine or its salt, propyl The group consisting of one or more of pancaine or its salt, chloroparacaine or its salt, cyclomethicaine or its salt, proparacaine or its salt, tetracaine or its salt, benzocaine or its salt, butacaine or its salt, butyrocaine or its salt, butylaminobenzoate or its salt, chloroprocaine or its salt, dimethocaine or its salt, oxybuprocaine or its salt, piperocaine or its salt, p-ethoxycaine or its salt, procaine or its salt, propoxycaine or its salt, tricaine or its salt, preferably lidocaine or its salt, and more preferably lidocaine hydrochloride.

[0054] Further, the content range of the local anesthetic is 0.1-10 mg / mL (such as 0.1 mg / mL, 0.2 mg / mL, 0.5 mg / mL, 0.8 mg / mL, 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL), preferably, the content range of the local anesthetic is 0.1-8 mg / mL, further preferably, the content range of the local anesthetic is 0.5-8 mg / mL, and even more preferably, the content range of the local anesthetic is 0.5-5 mg / mL.

[0055] In one embodiment of the present invention, the content of the local anesthetic is in the range of 3 mg / mL.

[0056] Furthermore, the water-soluble cellulose is selected from one or more of hydroxyethyl methylcellulose, hydroxypropyl methylcellulose, hydroxybutyl methylcellulose, ethyl methylcellulose and carboxymethyl cellulose, preferably hydroxypropyl methylcellulose.

[0057] Furthermore, the content of the water-soluble cellulose is in the range of 0.01 to 40 mg / mL, preferably 0.2 to 25 mg / mL, and more preferably 0.5 to 10 mg / mL.

[0058] The third aspect of the present invention provides a method for preparing a composition, comprising the following steps:

[0059] The cross-linked hyaluronic acid or its salt containing microspheres described in the first aspect is taken out after dialysis, and the pH value of the system is first adjusted to 10-11 with a hydrochloric acid solution, and then the pH value of the system is slowly adjusted to neutral with a lactic acid solution, and then a phosphate buffer solution and non-cross-linked hyaluronic acid or its salt are added, mixed evenly, and sterilized by wet heat to obtain a composition.

[0060] Furthermore, after adjusting the pH value of the system to neutral, a local anesthetic and / or water-soluble cellulose may be optionally added.

[0061] The fourth aspect of the present invention provides an application of the composition prepared by the cross-linked hyaluronic acid or its salt containing microspheres described in the first aspect or the composition described in the second aspect or the third aspect in the preparation of medicines, tissue engineering materials or cosmetics.

[0062] Preferably, the tissue engineering material comprises a soft tissue filling material, a cartilage repair material or a tissue engineering scaffold.

[0063] The fifth aspect of the present invention provides a non-medical cosmetic use of the cross-linked hyaluronic acid or its salt containing microspheres described in the first aspect or the composition described in the second aspect, or the composition prepared in the third aspect, for improving the appearance of the skin, smoothing wrinkles, or repairing the appearance of the face or body of a subject.

[0064] A sixth aspect of the present invention provides a non-medical method for improving the appearance of skin, smoothing wrinkles, or reshaping the face or body of a subject, comprising:

[0065] I) providing the cross-linked hyaluronic acid or its salt containing microspheres as described in the first aspect or the composition as described in the second aspect, or the composition prepared in the third aspect, and

[0066] II) injecting the cross-linked hyaluronic acid or its salt containing microspheres as described in the first aspect or the composition as described in the second aspect, or the composition prepared in the third aspect into the skin of the subject.

[0067] Furthermore, the composition of step II is injected into the dermis and / or subcutaneous tissue.

[0068] Beneficial effects of the present invention:

[0069] (1) The present invention uses high-molecular-weight HA and low-molecular-weight HA to cross-link under the conditions of large amount of alkali solution and small amount of alkali solution, and introduces microsphere components before cross-linking. The large amount of alkali solution can fully destroy the hydrogen bonding between HA, so that the high-molecular-weight and low-molecular-weight HA molecular chains are fully extended and stretched, and the molecular chains of low-molecular-weight HA can freely perform irregular translation or rotational motion while stretching. The high-molecular-weight and low-molecular-weight HA form interlaced cross-linking, so that the low-molecular-weight HA can be interlaced or erected between the high-molecular-weight HA, and a scaffold structure can be formed, which is convenient for the microspheres to enter the gel network. At the same time, the large amount of alkali solution causes a certain degradation of the molecular weight of HA, thereby cross-linking to form a loose structure with a large mesh spacing. During the HA cross-linking process, the microspheres can be evenly embedded in the loose structure, and the rigid microspheres are wrapped in the gel network, thereby enhancing the supporting performance of the gel; then, under the condition of small amount of alkali solution, , using low molecular weight HA as raw material, molecular chain entanglement is more common, easy to react to form a compact rubber ball mixed network structure, and then the compact rubber ball mixed network structure is further cross-linked with the aforementioned loose structure to make the overall structure more compact, and the microspheres can be more evenly dispersed in the formed multiple network structure, thereby increasing the loading capacity of the microspheres, so that the loading capacity of the microspheres can be as high as 75%; the presence of rigid balls in the gel not only increases the elastic modulus of the system, but also the multiple network structure can more effectively wrap the microspheres, which is more conducive to the wet heat sterilization resistance of the composition, and the loss rate of the elastic modulus after sterilization is low, which can more effectively protect the microspheres and reduce the degradation of the microspheres, so that the pH change caused by the degradation of the microspheres is smaller, and the degradation time and safety performance of the microspheres after implantation in the body are prolonged, thereby prolonging the effect of the microspheres stimulating collagen regeneration, and also improving the suspension performance of the microspheres in the composition, that is, the overall structural stability and long-term stability of the composition.

[0070] (2) The present invention can adjust the amount and molecular weight of high and low molecular weight hyaluronic acid or its salts according to the different implanted parts of the human body, so as to adjust the pore structure and mechanical properties of the cross-linked hyaluronic acid or its salts, thereby achieving precise matching of the gel filler with the injection site.

[0071] (3) The present invention forms a gel composition by combining a cross-linked hyaluronic acid or its salt gel containing microspheres with non-cross-linked hyaluronic acid or its salt, a local anesthetic or a water-soluble cellulose and other auxiliary materials. The gel composition can have good support and better tissue compatibility, and is more suitable for injection filling of the face, neck, hands and other parts of the body, especially the filling of the chin and mandibular margin. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 This is a schematic electron microscope diagram of the composition of Example 1.

[0073] Figure 2Schematic diagrams of the compositions of Example 1 and Comparative Example 4 before and after centrifugation (Left 1: the composition of Example 1 before centrifugation, Left 2: the composition of Comparative Example 4 before centrifugation, Right 1: the composition of Example 1 after centrifugation, Right 2: the composition of Comparative Example 4 after centrifugation).

[0074] Figure 3 These are morphological observation pictures of the composition of Example 1 after injection into a skin mimic, and 1 month, 2 months, and 3 months later.

[0075] Figure 4 This is a Masson staining image of the tissue 3 months after the composition of Example 1 was injected into the subcutaneous tissue of the back of SD rats. DETAILED DESCRIPTION

[0076] In order to more clearly understand the technical content of the present invention, the following embodiments are given in detail, the purpose of which is only to better understand the content of the present invention but not to limit the protection scope of the present invention.

[0077] Example 1

[0078] (1) Preparation of cross-linked sodium hyaluronate I′: Take 1.5 g of 1500 kDa sodium hyaluronate raw material, take 0.5 g of 600 kDa sodium hyaluronate raw material, add 20 mL of water, add 5 mL of 250 mg / mL sodium hydroxide solution, add 81.5 g of L-lactic acid-ethylene glycol copolymer microspheres and stir evenly, then add 0.06 mL of BDDE solution, mix evenly, and react at 25° C. for 20 h to obtain cross-linked sodium hyaluronate I′.

[0079] (2) Preparation of cross-linked sodium hyaluronate II′: Take 0.6 g of 600 kDa sodium hyaluronate raw material, add 6 mL of water, add 1.5 mL of 100 mg / mL sodium hydroxide solution to dissolve, add 27.1 g of L-lactic acid-ethylene glycol copolymer microspheres and stir evenly, then add 0.03 mL of BDDE solution, mix evenly, react at 25°C for 20 hours, and make the gel into micron particles to obtain cross-linked sodium hyaluronate II′.

[0080] (3) Preparation of cross-linked sodium hyaluronate containing microspheres: Add 37.5 mL of water to the cross-linked sodium hyaluronate I′ of step (1), stir evenly, add the micronized particles of cross-linked sodium hyaluronate II′ of step (2) and 0.3 g of 600 kDa sodium hyaluronate raw material to the cross-linked sodium hyaluronate I′, mix evenly, and continue the reaction at 25° C. for 6 h. After the reaction is completed, cross-linked sodium hyaluronate containing microspheres is obtained.

[0081] (4) The cross-linked sodium hyaluronate containing microspheres obtained in step (3) is dialyzed and the pH value of the system is first adjusted to about 10-11 with a hydrochloric acid solution having a mass concentration of 8%, and then the pH value of the system is slowly adjusted to neutral with a 30% lactic acid solution. Subsequently, 100 mL of phosphate buffer (10 g of disodium hydrogen phosphate, 4 g of sodium dihydrogen phosphate, and 1 g of potassium chloride are weighed and dissolved in 1000 mL of water), 0.26 g of lidocaine hydrochloride, and 0.4 g of 600 kDa sodium hyaluronate are added, and water is added to 194 mL. The mixture is mixed evenly and sterilized by wet heat to obtain a cross-linked sodium hyaluronate gel composition, which is defined as Composition 1.

[0082] Example 2

[0083] Only the molecular weight of sodium hyaluronate of 1500 kDa in step (1) of Example 1 was replaced by 900 kDa, and 600 kDa was replaced by 300 kDa, and the molecular weight of sodium hyaluronate of 600 kDa in steps (2)-(3) was replaced by 300 kDa, and the remaining steps were the same as in Example 1 to prepare composition 2.

[0084] Example 3

[0085] Only the molecular weight of sodium hyaluronate of 1500 kDa in step (1) of Example 1 was replaced by 2800 kDa, and 600 kDa was replaced by 1000 kDa, and the molecular weight of sodium hyaluronate of 600 kDa in steps (2)-(3) was replaced by 1000 kDa, and the remaining steps were the same as in Example 1 to prepare composition 3.

[0086] Example 4

[0087] Only the volume of 5 mL of sodium hydroxide in step (1) of Example 1 was replaced by 2 mL, and the volume of 1.5 mL of sodium hydroxide in step (2) was replaced by 0.6 mL, and the remaining steps were the same as in Example 1 to prepare composition 4.

[0088] Example 5

[0089] The "81.5 g of L-lactic acid-ethylene glycol copolymer microspheres" added in step (1) of Example 1 was replaced by "adding 34.0 g of L-polylactic acid microspheres", and the "27.1 g of L-lactic acid-ethylene glycol copolymer microspheres" added in step (2) was replaced by "adding 34.0 g of L-polylactic acid microspheres". In step (4), lidocaine hydrochloride was not added, and the remaining steps were the same as in Example 1 to prepare composition 5.

[0090] Example 6

[0091] The "81.5 g of L-lactic acid-ethylene glycol copolymer microspheres" added in step (1) of Example 1 was replaced by "adding 108.6 g of L-lactic acid microspheres", and the "27.1 g of L-lactic acid-ethylene glycol copolymer microspheres" added in step (2) was replaced by "adding 27.2 g of L-lactic acid microspheres", and before "adding water to 194 mL" in step (4), 0.19 g of hydroxypropyl methylcellulose was added, and the remaining steps were the same as in Example 1 to prepare Composition 6.

[0092] Comparative Example 1

[0093] Only the step (1) in Example 1, "adding 5 mL of 250 mg / mL sodium hydroxide solution" was replaced by "adding 5 mL of 100 mg / mL sodium hydroxide solution", and the remaining steps were the same as Example 1, to prepare a comparative composition 1.

[0094] Comparative Example 2

[0095] Only the step (1) in Example 1, "take 1.5 g of 1500 kDa sodium hyaluronate raw material and 0.5 g of 600 kDa sodium hyaluronate raw material" was replaced with "take 2 g of 1500 kDa sodium hyaluronate raw material", and the remaining steps were the same as Example 1, to prepare a comparative composition 2.

[0096] Comparative Example 3

[0097] Only the step (1) in Example 1, "take 1.5 g of 1500 kDa sodium hyaluronate raw material and 0.5 g of 600 kDa sodium hyaluronate raw material" was replaced with "take 2 g of 600 kDa sodium hyaluronate raw material", and the remaining steps were the same as Example 1, to prepare comparative composition 3.

[0098] Comparative Example 4

[0099] Preparation of cross-linked sodium hyaluronate gel: Take 2.9 g of 1500 kDa sodium hyaluronate raw material, add 20 mL of water, add 12.5 mL of 20 mg / mL sodium hydroxide solution to dissolve, add 108.6 g of polylactic acid microspheres and stir evenly, then add 0.1 mL of BDDE solution, mix evenly, react at 25° C. for 30 hours to obtain a cross-linked sodium hyaluronate gel containing microspheres. Then, the gel composition was prepared by the same operation as in Example 1 to prepare comparative composition 4.

[0100] Performance Testing

[0101] Performance Example 1

[0102] The composition of Example 1 was freeze-dried and observed using a scanning electron microscope. The structure of the composition is as follows: Figure 1 As shown. Figure 1It can be seen that the microspheres are evenly dispersed in the multiple network structure of the gel. The multiple network structure has a good encapsulation property for the microspheres and increases the loading capacity of the microspheres, making it difficult to separate from the network structure.

[0103] Performance example 2

[0104] Microsphere suspension performance: 1.3 g of the composition of Example 1 and Comparative Example 4 was placed in a 1.5 mL centrifuge tube and centrifuged at 9000 r / min for 30 min. After the centrifugation, the state of the microspheres and gel in the composition was observed to evaluate the stability of the composition. The results are as follows: Figure 2 shown.

[0105] As can be seen from the figure, after high-speed centrifugation, the composition of Comparative Example 4 showed stratification of microspheres and gel. From the sedimentation amount of microspheres, the microspheres were about 1 / 6 sedimented, indicating that the conventional one-time cross-linking method has a certain effect on the encapsulation and suspension of microspheres, but there is still a certain instability. After high-speed centrifugation, the microspheres and gel of the composition prepared by the preparation method of the present invention were basically not separated, indicating that the network structure of the microspheres and gel in the composition prepared by this invention can better encapsulate the microspheres, and can carry more microspheres, and has better supporting performance, and is more suitable for filling parts that require greater supporting force such as face, neck, hands and body parts.

[0106] Performance Example 3

[0107] The performance of the composition samples of Examples 1-6 and Comparative Examples 1-4 was tested, including elastic modulus and pH value. The specific testing method is as follows:

[0108] Elastic modulus: 2 g of the composition sample was taken respectively, and the modulus of the composition sample before and after wet heat sterilization was tested using a rheometer (TA) at 25° C. and a frequency of 1 Hz.

[0109] pH value: dilute the composition sample with water in equal mass proportion, and use a pH meter to measure the pH value of the sample before and after moist heat sterilization.

[0110] The characterization results are shown in Table 1.

[0111] Table 1 Elastic modulus and pH value data of different compositions before and after sterilization

[0112]

[0113] It can also be seen from Table 1 that the elastic modulus of Examples 1-6 is relatively high, the loss rate is within 15%, and the pH value changes slightly, which is significantly better than the modulus loss rate and pH value change of Comparative Examples 1-4. This shows that through the process of the present invention, high and low molecular weight HA are cross-linked under the conditions of a large amount of alkaline solution and low molecular weight HA is cross-linked under the conditions of a small amount of alkaline solution, and microsphere components are introduced before cross-linking. The large amount of alkaline solution can fully destroy the hydrogen bonding between HA, so that the high and low molecular weight HA molecular chains are fully extended and stretched, and the molecular chains of the low molecular weight HA can freely perform irregular translation or rotational motion while stretching. The high and low molecular weight HA form interlaced cross-linking, so that the low molecular weight sodium hyaluronate can be interlaced or erected between the high molecular weight sodium hyaluronate, and a scaffold structure can be formed to facilitate the microspheres to enter the gel network. At the same time, the large amount of alkaline solution causes a certain degradation of the molecular weight of HA, thereby cross-linking to form a loose structure with a large mesh spacing. During the HA cross-linking process, the microspheres can be evenly The rigid microspheres are uniformly embedded in the loose structure, and the rigid microspheres are wrapped in the gel network, which enhances the supporting performance of the gel; then, under the condition of a small amount of alkaline solution, low molecular weight HA is used as the raw material, the molecular chain entanglement is more common, and it is easy to react to form a compact gel ball mixed network structure, and then the compact gel ball mixed network structure is further cross-linked with the aforementioned loose structure to make the overall structure more compact, and the microspheres can be more evenly dispersed in the formed multiple network structure, thereby increasing the loading capacity of the microspheres, so that the loading capacity of the microspheres can be as high as 75%; the presence of rigid balls in the gel not only increases the elastic modulus of the system, but also the multiple network structure can more effectively wrap the microspheres, which is more conducive to the wet heat sterilization resistance of the composition, the loss rate of the elastic modulus after sterilization is low, and the microspheres can be more effectively protected, and the degradation of the microspheres is reduced, so that the pH change caused by the degradation of the microspheres is smaller, the degradation time and safety performance of the microspheres after implantation in the body are prolonged, and the suspension performance of the microspheres in the composition, that is, the overall structural stability and long-term stability of the composition are improved.

[0114] The modulus loss rates of Comparative Examples 1-4 are significantly inferior to those of Example 1, and the overall pH change rate is high. This is also because the amount of alkali in Comparative Example 1 is the same, making it difficult to form an interpenetrating chimeric structure. In Comparative Examples 2-3, since the molecular weight of the HA raw material during the first cross-linking is a single molecular weight, it is difficult to form a loose network structure, and the microspheres rarely enter the loose structure, and a solid wrapping structure cannot be formed. In Comparative Example 4, under conventional single molecular weight conditions, the gel network structure formed by cross-linking is single, and its mechanical properties such as strength and toughness are poor, and the composition has poor protection for the microspheres during wet heat sterilization. Therefore, the elastic modulus loss rate of the composition in Comparative Examples 1-4 is high, and the pH change rate is also high.

[0115] Performance Example 4

[0116] The degradation performance of the composition samples of Example 1 and Comparative Examples 1-4 was tested. The specific testing method was as follows: 10 g of the composition was added with 20 mL of 1 mol / L hydrochloric acid solution, and the degradation was carried out at 70° C. The time for complete degradation of the composition was observed.

[0117] The characterization results are shown in Table 2.

[0118] Table 2 Degradation data of different compositions

[0119]

[0120] As can be seen from Table 2, the degradation period of the composition of Example 1 is 58 days, which is much longer than the degradation time of the compositions in Comparative Examples 1-4. This is mainly because in Example 1, by introducing microspheres separately before chemical crosslinking, the microspheres can be more evenly dispersed in the formed multiple network structure, and the multiple network structure can more effectively wrap the microspheres, thereby improving their stability and prolonging the degradation time. In Comparative Examples 1-4, since it is difficult to form an effective multiple network structure, the dispersion and wrapping of the microspheres are poor. Therefore, the final degradation time is also short, which is not conducive to later clinical applications.

[0121] Performance example 5

[0122] Take the composition in Example 1, add toluidine blue and mix well, inject into the skin simulation, single point injection volume 1mL, place at 40℃ for accelerated test, the cycle is 3 months. Figure 3 As shown, after the composition was injected into the skin mimic, and 1 month, 2 months and 3 months after the injection, the ridge height of the skin mimic did not change significantly, indicating that the composition had good supporting effect and anti-degradation performance.

[0123] Performance example 6

[0124] The composition of Example 1 was injected into the subcutaneous tissue of the back of SD rats, with a single-point injection volume of 0.5 mL. After three months of conventional feeding, the injection site of the composition and the surrounding skin tissue were taken, sliced, and stained with Masson staining. The results are as follows: Figure 4 As shown in the figure, 3 months after the composition was implanted subcutaneously, the composition can still be observed in the subcutaneous tissue, and obvious new collagen can be seen in the filled part (marked by triangle in the figure), some collagen fibers are distributed around the microspheres in a wrapped manner, and new blood vessels can be seen in many places (marked by arrows in the figure), indicating that the composition of the present invention has a good effect of stimulating collagen regeneration.

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A cross-linked hyaluronic acid or a salt thereof containing microspheres, characterized in that: The preparation method of the cross-linked hyaluronic acid or its salt containing microspheres comprises the following steps: (1) mixing hyaluronic acid I or its salt, hyaluronic acid II or its salt, a first alkaline solution, microspheres and a cross-linking agent, and reacting them to obtain a cross-linked hyaluronic acid I′ or its salt; (2) mixing hyaluronic acid III or its salt, a second alkaline solution, microspheres and a cross-linking agent, and reacting them to obtain cross-linked hyaluronic acid II′ or its salt; (3) diluting the cross-linked hyaluronic acid I′ or its salt obtained in step (1) with water, adding the cross-linked hyaluronic acid II′ or its salt and hyaluronic acid IV or its salt obtained in step (2), mixing and reacting, thereby obtaining the cross-linked hyaluronic acid or its salt containing microspheres; The mass concentration of the first alkaline solution is higher than the mass concentration of the second alkaline solution; the molecular weight of the hyaluronic acid I is higher than the molecular weights of the hyaluronic acids II, III and IV.

2. The cross-linked hyaluronic acid or its salt containing microspheres according to claim 1, characterized in that: The concentration of the first alkaline solution in step (1) is 10 to 100 mg / mL, preferably 12 to 90 mg / mL, and more preferably 15 to 80 mg / mL; the concentration of the second alkaline solution in step (2) is 0.1 to 50 mg / mL, preferably 1 to 40 mg / mL, and more preferably 5 to 30 mg / mL.

3. The cross-linked hyaluronic acid or its salt containing microspheres according to claim 1, characterized in that: The molecular weight of the hyaluronic acid I is 900-3000 kDa, preferably 1000-2000 kDa, more preferably 1200-1600 kDa; the molecular weight of the hyaluronic acids II, III and IV is 100-1000 kDa, preferably 300-800 kDa, more preferably 400-700 kDa.

4. The cross-linked hyaluronic acid or its salt containing microspheres according to any one of claims 1 to 3, characterized in that: The mass ratio of hyaluronic acid I or its salt to hyaluronic acid II or its salt in step (1) is 2-10:1, preferably 3-9:1; Preferably, the ratio of the cross-linked hyaluronic acid I′ or its salt to the cross-linked hyaluronic acid II′ or its salt is 1-10:1, preferably 2-6:1; Preferably, the amount of hyaluronic acid IV or its salt added is 5%-30% of hyaluronic acid I or its salt relative to hyaluronic acid I or its salt.

5. The cross-linked hyaluronic acid or its salt containing microspheres according to any one of claims 1 to 3, characterized in that: The reaction temperature in steps (1), (2) and (3) is 20 to 30° C.; preferably, the reaction time in steps (1), (2) and (3) is 4 to 30 hours.

6. The cross-linked hyaluronic acid or its salt containing microspheres according to any one of claims 1 to 3, characterized in that: The hyaluronate is selected from any one of sodium hyaluronate, potassium hyaluronate, calcium hyaluronate, magnesium hyaluronate, ammonium hyaluronate, tetrabutylammonium hyaluronate, bismuth hyaluronate and zinc hyaluronate, preferably sodium hyaluronate; Preferably, the degree of cross-linking of the obtained microsphere-containing cross-linked hyaluronic acid or its salt is 1% to 6%, preferably 1.5% to 5%; Preferably, the alkaline solution is selected from: a solution prepared by one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium sulfite, and potassium sulfite, more preferably a sodium hydroxide solution; Preferably, the cross-linking agent is selected from: one or a combination of two or more of 1,4-butanediol diglycidyl ether, divinyl sulfone, polyethylene glycol, genipin and carbodiimide, more preferably 1,4-butanediol diglycidyl ether.

7. The cross-linked hyaluronic acid or its salt containing microspheres according to any one of claims 1 to 3, characterized in that: The microspheres are selected from: one or more of polyester microspheres, collagen microspheres, silk fibroin microspheres, and hydroxyapatite microspheres; preferably polyester microspheres; more preferably, polyester microspheres are one or more of PLLA, PDLA, PDLLA, PLGA, PMMA, PCL, PEG-PLLA, and HA-PLLA.

8. The cross-linked hyaluronic acid or its salt containing microspheres according to any one of claims 1 to 3, characterized in that: The content of microspheres in the cross-linked hyaluronic acid or its salt containing microspheres is: 10% to 75%, preferably 15% to 70%, more preferably 20% to 65%; Preferably, the dosage ratio of the microspheres in steps (1) and (2) is 1-5:

1.

9. A composition, characterized in that The composition comprises: the cross-linked hyaluronic acid or its salt containing microspheres as described in any one of claims 1 to 8, and also comprises non-cross-linked hyaluronic acid or its salt, phosphate buffer, and optionally a local anesthetic and / or water-soluble cellulose.

10. The composition according to claim 9, characterized in that The mass concentration of the cross-linked hyaluronic acid or its salt in the composition is 8 to 30 mg / mL; Preferably, the non-cross-linked hyaluronate is selected from any one of non-cross-linked sodium hyaluronate, non-cross-linked potassium hyaluronate, non-cross-linked calcium hyaluronate, non-cross-linked magnesium hyaluronate, non-cross-linked ammonium hyaluronate, non-cross-linked tetrabutylammonium hyaluronate, non-cross-linked bismuth hyaluronate and non-hyaluronate zinc, preferably non-cross-linked sodium hyaluronate; Preferably, the concentration of the non-cross-linked hyaluronic acid or its salt is 0.2 to 10 mg / mL; Preferably, the molecular weight of the non-cross-linked hyaluronic acid or its salt is 100 to 1000 kDa; Preferably, the phosphate buffer comprises disodium hydrogen phosphate, sodium dihydrogen phosphate and potassium chloride; Preferably, the local anesthetic is selected from the group consisting of: amide type and ester type or a combination thereof; Preferably, the water-soluble cellulose is selected from one or more of hydroxyethyl methylcellulose, hydroxypropyl methylcellulose, hydroxybutyl methylcellulose, ethyl methylcellulose and carboxymethyl cellulose.

11. A method for preparing the composition according to claim 9 or 10, comprising the steps of: The cross-linked hyaluronic acid or its salt containing microspheres is taken out after dialysis, and the pH value of the system is first adjusted to 10-11 with a hydrochloric acid solution, and then the pH value of the system is adjusted to neutral with a lactic acid solution, and then a phosphate buffer solution and non-cross-linked hyaluronic acid or its salt are added, mixed, and sterilized by wet heat to obtain a composition.

12. The preparation method according to claim 11, characterized in that: After adjusting the pH value of the system to neutral, a local anesthetic and / or water-soluble cellulose may be optionally added.

13. Use of the cross-linked hyaluronic acid or its salt containing microspheres as claimed in any one of claims 1 to 8, or the composition as claimed in any one of claims 9 to 10, or the composition prepared by the preparation method as claimed in any one of claims 11 to 12 in the preparation of medicines, tissue engineering materials or cosmetics; Preferably, the tissue engineering material comprises a soft tissue filling material, a cartilage repair material or a tissue engineering scaffold.

Citation Information

Patent Citations

  • Cross-linked sodium hyaluronate gel and its preparation method

    CN106279726B

  • Preparation method of cross-linked hyaluronic acid gel

    CN112940300B

Cited By

  • Composition comprising microspheres and crosslinked hyaluronic acid or salt thereof, and preparation method therefor and use thereof

    WO2026113956A1